2020
DOI: 10.1177/1945892420956530
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Clinical Findings in Primary Headache Syndrome Versus Chronic Rhinosinusitis

Abstract: Background Primary headache syndrome (PHS) patients frequently present to otolaryngologists with sinonasal complaints and diagnosis of chronic rhinosinusitis (CRS) due to symptomatic overlap. In this study, we compare demographic, subjective, and objective clinical findings of patients with PHS versus CRS. Methods We retrospectively reviewed a database of patients presenting to a single tertiary care Rhinology clinic from December 2011—July 2017. Sino-Nasal Outcome Test-22 (SNOT) scores and Lund-Kennedy endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Our multivariate model demonstrated that while higher nasal domain scores were associated with sinusitis, higher ear/facial domain scores were associated with NRFP. This is consistent with studies by Wu et al and Sharbel et al, which also reported prominence of ear/facial symptoms in relation to nasal symptoms in patients with NRFP 11,17 . Indeed, our clinical experience has been that patients with NRFP will often complain of ear fullness and vestibular problems in the setting of normal ear exams.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our multivariate model demonstrated that while higher nasal domain scores were associated with sinusitis, higher ear/facial domain scores were associated with NRFP. This is consistent with studies by Wu et al and Sharbel et al, which also reported prominence of ear/facial symptoms in relation to nasal symptoms in patients with NRFP 11,17 . Indeed, our clinical experience has been that patients with NRFP will often complain of ear fullness and vestibular problems in the setting of normal ear exams.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with studies by Wu et al and Sharbel et al, which also reported prominence of ear/facial symptoms in relation to nasal symptoms in patients with NRFP. 11,17 Indeed, our clinical experience has been that patients with NRFP will often complain of ear fullness and vestibular problems in the setting of normal ear exams. With increasing evidence from multiple institutions supporting this, we believe that this can serve as an important clinical differentiator in everyday practice.…”
Section: Discussionmentioning
confidence: 99%
“…Primary headache disorder patients had significantly higher ear/facial domain and sleep domain scores while CRS patients had a significantly higher rhinologic domain score 22 …”
Section: Resultsmentioning
confidence: 96%
“…The ear/facial domain can be a significant negative predictor of CRS (Cutoff 4, NPV 0.828, PPV 0.581, Sensitivity 0.894, Specificity 0.442) 22 …”
Section: Resultsmentioning
confidence: 99%
“…Distinguishing these headache disorders from chronic rhinosinusitis can be challenging and often requires consultation with headache specialists when sinonasal inflammation is not present. In a retrospective study, Sharbel et al 13 sought to compare patients with PHS vs CRSwPHS and CRS alone. They measured SNOT-22 scores and Lund-Kennedy endoscopy scores and Lund-MacKay CT scores (when available).…”
Section: Olfaction and Beyond: Advancing Our Understanding For Evidence-based Practicementioning
confidence: 99%